Deubiquitinase OTUD3: a double-edged sword in immunity and disease - Xu, Qiao; He, Lan; Zhang, Shubing; Di, Xiaotang; Jiang, Hao (Frontiers in Cell and Developmental Biology, 2023)
Deubiquitination is an important form of post-translational modification that regulates protein homeostasis. Ovarian tumor domain-containing proteins (OTUDs) subfamily member OTUD3 was identified as a deubiquitinating enzyme involved in the regulation of various physiological processes such as immunity and inflammation.Disturbances in these physiological processes trigger diseases in humans and animals, such as cancer, neurodegenerative diseases, diabetes, mastitis, etc. OTUD3 is aberrantly expressed in tumors and is a double-edged sword, exerting tumor-promoting or anti-tumor effects in different types of tumors affecting cancer cell proliferation, metastasis, and metabolism. OTUD3 is regulated at the transcriptional level by a number of MicroRNAs, such as miR-520h, miR-32, and miR101-3p. In addition, OTUD3 is regulated by a number of post-translational modifications, such as acetylation and ubiquitination. Therefore, understanding the regulatory mechanisms of OTUD3 expression can help provide insight into its function in human immunity and disease, offering the possibility of its use as a therapeutic target to diagnose or treat disease.